The Mediating Role of Emotional Exhaustion in the Relationship between Abusive Supervision and Employee Cyberloafing Behaviour. - Khan, Jawad; Saeed, Imran; Ali, Amna; Nisar, Hena Gul (Journal of Management and Research, 2021)
Cyberloafing is becoming a common problem in every organization that directly affects organizational productivity. In this study we are going to study the influence of abusive supervision on cyberloafing, further, we are studying the mediating effect of emotional exhaustion generated due to abusive supervision behaviour, motivating employees towards cyberloafing. The data were collected from 150 employees working in Saif Textile Mills Ltd & Kohat Textile Mills Ltd, Pakistan through questionnaires. The study sample was drawn using a convenience sampling technique. This study used SPSS 25 and process Hayes (2013) model 4 for data analysis and for model fitness we used CFA (AMOS 22). The data findings demonstrate that abusive supervision significantly and positively affects cyberloafing and also emotional exhaustion mediates this relation significantly. Therefore we conclude that abusive supervision is the main factor for employees to be exhausted and ultimately move towards cyberloafing. Based on these finding managers plays a vital role to maintain organization environment friendly.